Penerapan Pendekatan CRT (Culturally Responsive Teaching) dalam Meningkatkan Keterampilan Menulis Surat Pribadi Siswa SMP - Ocktavia, Debby; Rosdiana, Rina; Nurjannah, Nurjannah (Fakultas Sastra Universitas Muslim Indonesia, 2024)
The purpose of this study was to analyze the improvement of personal letter-writing skills by applying the CRT (Culturally Responsive Teaching) approach to students of SMP Negeri 3 Kota Bogor. This study is a classroom action research with subjects of Class VII students of SMP Negeri 3 Kota Bogor which was carried out in two cycles. Data collection techniques were in the form of observation, assessment of personal letter-writing skills, and photo and video documentation. Data analysis techniques used qualitative and quantitative descriptive analysis techniques. The results of the study showed that the average value of all aspects observed in writing personal letters of students in cycle 1, students who had not completed were 20 people with a percentage of 64.51% and students who had completed were only 11 people with a rate of 35.48%. Furthermore, in cycle 2 there was an increase, namely 25 students entered the complete category with a percentage of 81% and students in the uncompleted category were 6 people with a rate of 19%. Thus, the CRT approach succeeded in improving the personal letter-writing skills of class VII students of SMP Negeri 3 Kota Bogor.